The Roman Adversarial Dialogue in Eighteenth-Century Political Satire. (November 2015) - Bucknell, Clare
Abstract : This article examines the use of the Roman satiric dialogue in eighteenth-century political verse. It studies partisan satires that pit their speakers against a cautionary interlocutor ( adversarius ) in imitation of Horace's Satire 2.1 and Persius' Satire 1. It begins with an overview of Pope's use of the dialogue form in his Imitations of Horace, and his shift in the later 1730s to a model of antagonistic encounter between ideological opponents in the style of Persius. Its main body is an examination of later eighteenth-century satires that find alternative political uses for Persius' dialogue form to those of Pope and the Whig Patriot satirists who followed his lead. It studies Thomas Newcomb's inversion of Pope's Epilogue to the Satires for the purposes of ministerial propaganda; Charles Churchill's variations on the dialogue form under the banner of Wilkesite opposition; and Peter Pindar's comic burlesque of the traditional postures of dialogic satire in One Thousand Seven Hundred and Ninety-Six . The article reveals the Roman dialogue to have been a distinctively flexible framework for eighteenth-century satirists, capable of accommodating positions and arguments on both sides of the partisan divide.